Organic–inorganic hybrid perovskite for low-cost and high-performance xerographic photoreceptors. Issue 35 (21st June 2021) - Gu, Wei-Min; Wang, Chuanxi; Gao, Cai-Yan; Fan, Xin-Heng; Yang, Lian-Ming; Jiang, Ke-Jian
Abstract : MAPbI3 perovskite is first used as a light-absorbing charge-generating material for xerographic photoreceptors. The resultant photoreceptor exhibits excellent xerographic properties, and good environmental and electrical cycling stability. Abstract : Solution-processable organic–inorganic hybrid perovskites are being widely investigated for many applications, including solar cells, light-emitting diodes, photodetectors, and lasers. Herein, we report, for the first time, successful fabrication of xerographic photoreceptors using methylammonium lead iodide (CH3 NH3 PbI3 ) perovskite as a light-absorbing material. With the incorporation of polyethylene glycol (PEG) into the perovskite film, the ion migration inherent to the perovskite material can be effectively suppressed, and the resulting photoreceptor exhibits a high and panchromatic photosensitivity, large surface potential, low dark decay, and high environmental resistance and electrical cycling stability. Specifically, the energies required to photodischarge one half of the initial surface potential ( E 0.5 ) are 0.074 μJ cm −2 at 550 nm and 0.14 μJ cm −2 at 780 nm, respectively. The photosensitivites outmatch those of the conventionally used organic pigments having narrow spectral responses. Our findings inform a new generation of highly efficient and low-cost xerographic photoreceptors based on perovskite materials.